PENGARUH ATRAKSI WISATA, AMENITAS DAN AKSESIBILITAS TERHADAP KEPUTUSAN BERKUNJUNG PADA OBJEK WISATA RELIGI MAKAM KH. ABDURRAHMAN WAHID - Muharromah, Gabriele Lailatul; Anwar, Moch Khoirul (Jurnal Ekonomika dan Bisnis Islam, 2020)
Every year, the number of tourist visit religious tourist attraction, KH. Abdurrahman Wahid cemetery increases. The tourist decision to visit a tourist attraction place can be influenced by several factors, such as tourist attractions, amenities and accessibility. The purpose of this research is to know the impact of tourist attractions, amenities, and accessibility to the decision of visit on the religious tourism KH. Abdurrahman Wahid cemetery. The research methods used are quantitative research and used multiple linear regression analyses. The results showed that tourist attraction variables and accessibility variables were positive and significant to the visiting decision. But the variable of amenities had no significant effect on the visiting decision. Simultaneously variable tourist attractions, amenities and accessibility affected the variable of visiting decisions.